Policy Implications of the TikTok Shop E-Commerce Platform in the Contemporary Era: A Siyasah Syar'iyyah Perspective - Aneka Rahma; Khairuddin; Anita Niffilayani; Mohammad Eisa Ruhullah (MILRev: Metro Islamic Law Review, 2024)
This study explores the policy implications of the TikTok Shop e-commerce platform in the contemporary era through the lens of Siyasah Syar'iyyah. As one of the fastest-growing e-commerce platforms, TikTok Shop has significantly influenced the dynamics of digital transactions and interactions between consumers and businesses. However, with the rapid pace of digital transformation, there is a need for policy evaluation that effectively regulates transactions and aligns with Shariah principles. The research adopts an empirical juridical approach, employing field studies and in-depth interviews as the primary methods for data collection. Interviews were conducted with Islamic economic experts, e-commerce practitioners, and relevant policymakers. The findings indicate that existing TikTok Shop policies can be aligned with Siyasah Syar'iyyah principles by emphasizing justice (al-‘adalah) and public benefit (al-Maslahah). This includes ensuring equal opportunities for small and medium-sized enterprises (SMEs) and other small-scale entrepreneurs and maintaining that products sold meet Shariah standards, such as being halal and providing transparent product information. However, key challenges in implementing Shariah-based regulations include monitoring the dynamic content and transactions on the platform and addressing the use of algorithms that may be unfair or manipulative. To address these challenges, strict yet adaptive regulations are needed to keep up with technological advancements. The academic contribution of this study lies in advancing a more relevant and practical application of Siyasah Syar'iyyah for regulating digital platforms in the modern era. Furthermore, it provides policy recommendations to create a fairer, more transparent e-commerce ecosystem that upholds Shariah values, delivering long-term benefits for society and the global digital industry.